Kuat Tekan Dan Kuat Tarik Belah Beton OPC Dan OPC Abu Sekam Padi Di Lingkungan Gambut - Yogie Pranata; Ismeddiyanto Ismeddiyanto; Monita Olivia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The objective of the study is to investigate the mechanical properties of concrete with different replacement levels of Ordinary Portland Cement (OPC) by Rice Husk Ash (RHA). Two RHA replacement levels were considered in the study which is 5% and 10% by the weight of cement. After the specified initial curing period (28 days), specimens were immersed directly in peat water canal for 28 days. The mechanical properties was evaluated by measuring the compressive strength and tensile strength of the concrete specimens. The result shows that the compressive strength of OPC concrete is higher than OPC concrete using RHA as cementitious materials. A replacement level of 10% RHA in OPC concrete performs and shows better tensile strength than other replacements.Keywords : Mechanical properties, OPC, Rice Husk Ash (RHA), peat water